2023
DOI: 10.3389/fmicb.2023.1254598
|View full text |Cite
|
Sign up to set email alerts
|

Application of multi-functional lactic acid bacteria strains in a pilot scale feta cheese production

Christina S. Kamarinou,
Olga S. Papadopoulou,
Agapi I. Doulgeraki
et al.

Abstract: Feta cheese is the most recognized Greek Protected Designation of Origin (PDO) product in the world. The addition of selected autochthonous lactic acid bacteria (LAB) strains to cheese milk as adjunct cultures is gaining more attention, since they can impact the nutritional, technological and sensory properties of cheeses, as well as improve the safety of the product. The aim of this study was to produce Feta cheese with enhanced quality and safety, and distinctive organoleptic characteristics by applying auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…However, LAB tend to exhibit greater tolerance to these stresses, which makes them valuable contributors to the fermentation process and the preservation of various foods [ 53 ]. Here, we annotated several genes involved in survival under these harsh conditions ( Table 3 ), in agreement with previous data on the viability of the strain during yoghurt and feta cheese production [ 7 , 18 ]. Numerous studies have also identified these loci within the genome of the Lc.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, LAB tend to exhibit greater tolerance to these stresses, which makes them valuable contributors to the fermentation process and the preservation of various foods [ 53 ]. Here, we annotated several genes involved in survival under these harsh conditions ( Table 3 ), in agreement with previous data on the viability of the strain during yoghurt and feta cheese production [ 7 , 18 ]. Numerous studies have also identified these loci within the genome of the Lc.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, whole-genome sequencing, annotation and comprehensive bioinformatic analyses were performed to provide deeper understanding of the functional, technological, and safety properties of Lc. paracasei SRX10, a multifunctional strain that has previously been employed as an adjunct culture in yoghurt and feta cheese production [ 7 , 18 ]. The genome of the strain consists of a chromosome with a length of 2.8 Mb and a GC content of 46.4%, coding for 2711 putative proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations